Meeting the oral health needs of 12-year-olds in China: human resources for oral health - Xiangyu Sun; Eduardo Bernabé; Xuenan Liu; Shuguo Zheng; Jennifer E. Gallagher (BMC, 2017)
Abstract Background An appropriate level of human resources for oral health [HROH] is required to meet the oral health needs of population, and enable maximum improvement in health outcomes. The aim of this study was to estimate the required HROH to meet the oral health needs of the World Health Organization [WHO] reference group of 12-year-olds in China and consider the implications for education, practice, policy and HROH nationally. Methods We estimated the need of HROH to meet the needs of 12-year-olds based on secondary analysis of the epidemiological and questionnaire data from the 3rd Chinese National Oral Health Survey, including caries experience and periodontal factors (calculus), dentally-related behaviour (frequency of toothbrushing and sugar intake), and social factors (parental education). Children's risk for dental caries was classified in four levels from low (level 1) to high (level 4). We built maximum and minimum intervention models of dental care for each risk level, informed by contemporary evidence-based practice. The needs-led HROH model we used in the present study incorporated need for treatment and risk-based prevention using timings verified by experts in China. These findings were used to estimate HROH for the survey sample, extrapolated to 12-year-olds nationally and the total population, taking account of urban and rural coverage, based on different levels of clinical commitment (60-90%). Results We found that between 40,139 and 51,906 dental professionals were required to deliver care for 12-year-olds nationally based on 80% clinical commitment. We demonstrated that the majority of need for HROH was in the rural population (72.5%). Over 93% of HROH time was dedicated to prevention within the model. Extrapolating the results to the total population, the estimate for HROH nationally was 3.16-4.09 million to achieve national coverage; however, current HROH are only able to serve an estimated 5% of the population with minimum intervention based on a HROH spending 90% of their time in providing clinical care. Conclusions The findings highlight the gap between dental workforce needs and workforce capacity in China. Significant implications for health policy and human resources for oral health in this country with a developing health system are discussed including the need for public health action.